Effect of Waterproofing Treatment on Mechanical Properties of Bamboo - Lei Yang; Dongming Li; Lixiang Yu (BioResources)
Longitudinal tensile, longitudinal compressive, and flexural tests of bamboo from different regions were carried out, and the values of strength and elastic modulus were obtained. The probability distribution models of mechanical properties of bamboo in different regions were studied based on the data. The effects of no waterproofing treatment, tung oil treatment, and wood wax oil treatment on mechanical property degradation of bamboo were studied in response to 7 days of soaking. The main conclusions include: the mechanical properties of bamboo produced in Yunnan Province were the highest, followed by Jiangxi Province, and the lowest in Zhejiang Province. The Weibull distribution model achieved a good fit for all mechanical properties. With the increase of soaking time, the mechanical properties of bamboo were degraded. Degradation in the control group was the highest, followed by the wood wax oil group, and tung oil group was the lowest. On the 7th day, the average mechanical properties of the control group had decreased by 32.0%, the tung oil group by 14.5%, and the wood wax oil group by 25.6%. Through comprehensive comparison, it was evident that tung oil treatment provided the best waterproofing effect for bamboo.